The Relevance of Administrative Accountability and Social Accountability and its Impact on Welfare Improvement: DIY Province Case Study - Nur Faidati; Muhamad Khozin (JIP (Jurnal Ilmu Pemerintahan) : Kajian Ilmu Pemerintahan dan Politik Daerah, 2020)
This study intends to trace the relationship between administrative accountability and social accountability and its impact on the level of welfare of the people of the Special Region of Yogyakarta. For this purpose, case study research is carried out with a qualitative approach. This study uses data collection techniques such as desk study and interviews. Desk study is carried out through secondary data tracking, while the interviews were conducted with Bappeda and Internal Supervisory Board. The findings of the research show that a number of mechanisms prepared by the DIY Government in the framework of overseeing the implementation of development are not sufficient to contribute on improving the welfare of the community. This is because the existing mechanism is more administrative and not substantive (social). The mechanism prepared by the Government of the Special Region of Yogyakarta does not provide space for community participation. The space of participation provided is more formalistic. Consequently, the substantive accountability that provides a way for the operation of administrative and social accountability is not found.